Internet Economics of Distributed Systems* - Gottinger, Hans W (Archives of Business Research, 2015)
A macroscopic view of Internet -based distributed computer systems reveals the complexity of the organization and management of the resources and services they provide. The complexity arises from the system size (e.g. number of systems, number of users) and heterogeneity in applications (e.g. online transaction processing, e-commerce, multimedia, decision support, intelligent information search) and resources (CPU, memory, I/O bandwidth, network bandwidth and buffers, etc.) In a large distributed system , the set of systems, users and applications is continuously changing. In this paper we address some of the management issues of providing Quality of Service (QoS), pricing, and efficient allocation of resources (computational resources) in networks and systems facilitated through economic mechanism design. Keywords: Internet Economics, Network Economy, Distributed Systems, Mechanism Design, Performance Management